Weight change at 12 months among hormonal contraceptive users at Nur Sejahtera Clinics of National Population and Family Development Board (LPPKN): a retrospective study - Zain, Hanis Harlida; Theng, Cheong Ai; Abdul Manaf, Abdul Hadi (Faculty of Medicine and Health Sciences UPM, 2023)
Introduction: Weight gain was among the most common side effects that caused women to discontinue using hormonal contraception. However, previous literature had reported inconsistent findings of the association between hormonal contraception and weight change. This study aimed to determine the impact of hormonal contraceptive use on weight gain and factors associated with weight gain among the hormonal contraceptive users. Methods: A retrospective cohort study was conducted in four Nur Sejahtera Clinics using universal sampling method between September to November 2021. This study recruited women that had been using the hormonal contraception continuously for at least 12 months and had their weight measure at baseline and 12 months. Sociodemographic and clinical characteristic of the participant, weight measurement at baseline and 12 months and the type of hormonal contraception used were retrieved from the records. Multiple logistic regression was used to examine the factors associated with >5 weight gain. Results: A total of 366 samples were recruited. About one-third (33.6) of hormonal contraceptive users had their weight gain more than 5 from their baseline weight. The risk factor for weight gain more than 5 were women with aged less than 40 years (AOR=2.09; 95 CI:1.26,3.45) and Etonogestrel (ENG) implant user (AOR = 7.91; 95 CI:2.69,23.24). Conclusion: One third of the hormonal contraception users had their weight gain greater than 5. Lifestyle intervention to prevent weight gain could be targeted at high-risk users who are less than 40 years old and those on ENG implant.